anonymous
  • anonymous
solve the equation x+1=sqrt/19-x
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
So I think you are trying to solve the equation: \[x+1=\sqrt{19-x}\] Right? If not, let me know... To solve this equation you need to square both sides... the square cancels out the square root but you have to be careful! Squaring both sides of an equation can give solutions that aren't of the original equation. These are called extraneous solutions... \[(x+1)^2=(\sqrt{19-x})^2\]
anonymous
  • anonymous
i dont kno how to write it step by step i dont get it
anonymous
  • anonymous
O.k., \[(x+1)^2= (\sqrt{19-x})^2\] \[(x+1)(x+1)=19-x\] \[x^2+x+x+1=19-x\] \[x^2+2x+1=19-x\] -19 +x -19 +x \[x^2+3x-18=0\] (x-3)(x+6)=0 so either x = 3 or x = -6 Now you have to check your answer in the original equation

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
if x = 3, \[x+1 = \sqrt{19-x}\] becomes \[(3)+1 = \sqrt{19-(3)}\] which reduces to \[4 = \sqrt{16}\] which is true so x = 3 is a solution. if x = -6, \[x+1 = \sqrt{19-x}\] becomes \[(-6)+1 = \sqrt{19-(-6)}\] which reduces to \[x+1 = \sqrt{19-x}\] which becomes \[-5 = \sqrt{25}\] which is -5 = 5 which isn't true so x is not equal to -6 Therefore your only solution is x = 3
anonymous
  • anonymous
Is that enough steps? :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.